Leveraging Marker-based Augmented Reality to Enhance Simplified Representation Learning in Mechanical Drawing : A Practical Studies in The Mechanical Engineering Curriculum - Wardhani, Rivai (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to develop AR technology of simplified representations based on ISO standards and to quantify the efficiency and contribution of developed AR technology in assisting students in learning mechanical drawing. This research proposed a marker-based AR application development, intended for teaching simplified representations, named Augmented Reality Penyederhanaan Gambar - ARPeGa, and an experimental study to quantify the user experience (UX) using the User Experience Questionnaire (UEQ). A pilot study involving 38 mechanical engineering students was conducted to evaluate the impact of AR involvement on user experience. In addition, the UEQ data analysis tool version 11 was used.Â  The UEQ results showed attractiveness was excellent (1.87), while efficiency, dependability, stimulation, and novelty were good (1.63, 1.60, 1.63, and 1.22 respectively). And perspicuity was categorized as â€œabove averageâ€ (1.51). This studyâ€™s outcomes demonstrate that using 3D model visualization in the AR application strengthens user experiences to understand simplified representations. Overall, the application has a â€˜goodâ€™ level in some categories: efficiency, dependability, stimulation, and novelty.